REDISCOVERING THE COMMUNITY BOND: A CASE STUDY OF THE RELEVANCE OF TRADITIONAL WET MARKET IN PROMOTING SPONTANEOUS COMMUNITY BONDING IN CONTEMPORARY CONTEXT AND THE FUTURE DIRECTION OF THIS COMMUNAL SPACE - ZHENG CHENXI CHELSEA (2014)
Master's